ANALISIS KESESUAIAN MATERI IPA BUKU SISWA KELAS IV SD TERHADAP STANDAR ISI KURIKULUM 2013 - Mera Putri Dewi; Taufina Taufina (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
Science learning is one of the contents of learning in the 2013 curriculum. Learning material in science content has been contained in integrated thematic books. Although the books published by the government have been prepared as well as possible but according to the changing times, the books will continue to be improved and changed to meet the development of the era itself. Therefore, inputs are needed to improve the quality of the book. Therefore, the Science Material in the student book must refer to the 2013 curriculum content standards. The purpose of this study is to see the suitability of the grade IV science books for elementary school students to the 2013 curriculum content standards. The research method used is content analysis. From the results of the analysis it can be seen that from the nine scope of the scope of natural science materials in the 2013 curriculum content standards there are three science materials that are not presented in student books, namely the shape of objects, plant breeding, and materials on climate and weather. In addition, there are two additional materials in the student book which are about the properties of sound and the properties of light that are not contained in the 2013 curriculum content standardsKeywords: Science Materials, Student Books, Content Standard, 2013 Curriculum